Colonization and aflatoxin formation by aspergillus spp on brown rices differing in endosperm properties - Ilag, Lina L.; Juliano, Bienvenido O. (Wiley, 1982)
Aspergillus flavus Link and A. parasiticus Speare differed in sporulation and aflatoxin B1 formation on 15 brown rices differing in starch properties and protein content. There was no significant correlation between the degree of spore formation by the fungi and the amount of aflatoxin they produced in the rice samples. Differences in sporulation and aflatoxin production were not correlated with the dimensions (weight and hardness) of brown rice nor with the protein content, alkali spreading value, amylose content and gel viscosity of milled rice. Aflatoxin B1 was mainly concentrated in the bran layers. Histological examination revealed that the hyphae of A. flavus entered through cracks in the periderm and penetrated the endosperm.